Relation of The Intrinsic Value Of Companies and Share Prices on The Stock Exchanges of Central and Eastern European Transition Countries - Alibegović, Džafer (Naše gospodarstvo/Our economy, 2013)
This paper examines the relationship of the intrinsic value of companies and the price of their shares on stock exchanges. The research is based on an analysis of indicators of intrinsic values and market price trends among 37 companies from 7 stock exchanges in central and eastern European transition countries. Although a number of studies have confirmed a strong relationship between the intrinsic value of the company and the market price of shares on the stock markets of developed countries, this paper finds that such relationships in the case of companies from transition stock exchanges do not exist. Rather, a direct and very strong relationship exists among the share market price trends and among the leading market indexes of the observed stock exchanges.